China’s Weibo: is faster different? - Sullivan, Jonathan (SAGE Publications, 2013)
The popularization of microblogging in China represents a new challenge to the state’s regime of information control. The speed with which information is diffused in the microblogosphere has helped netizens to publicize and express their discontent with the negative consequences of economic growth, income inequalities and official corruption. In some cases, netizen led initiatives have facilitated the mobilization of online public opinion and forced the central government to intervene to redress acts of lower level malfeasance. However, despite the growing corpus of such cases, the government has quickly adapted to the changing internet ecology and is using the same tools to help it maintain control of society by enhancing its claims to legitimacy, circumscribing dissent, identifying malfeasance in its agents and using online public opinion to adapt policy and direct propaganda efforts. This essay reflects on microblogging in the context of the Chinese internet, and argues that successes in breaking scandals and mobilizing opinion against recalcitrant officials should not mask the reality that the government is utilizing the microblogosphere to its own advantage.